Correlation between the Pollution Risk of Wells and the Presence of Escherichia coli Bacteria at Daroy Kameu Village Darul Imarah subdistrict Aceh Besar district in 2017 - Zulfikar Zulfikar; Ratina Putri; Wiwit Aditama (HIGIENE: Jurnal Kesehatan Lingkungan, 2019)
Wells are one of the means of clean water supplier for rural and urban communities. The risk of bacterial pollution in wells is very large since it is influenced by the lack of concern and knowledge of the well owners in carrying out maintenance. This study aims to find out the correlation between the pollutionrisk of wells and the presence of Escherichia coli bacteria at Daroy Kameu Village, Darul ImarahSubdistrict, Aceh Besar District, in 2017.This study was a descriptive analytic study with a cross sectional design with the samples of 30 wells. The study was conducted in March to April 2017 at Daroy Kameu Village, Darul Imarah Subdistrict, Aceh Besar District. Data analysis was  conducted with Chi-square test.Form the results of data analysis ir can beconcluded that there was a correlation between the level of pollution risk of wells and the presence of E. coli bacteria in well water (p = 0.021), there was a relationship between the distance of dug wells with the presence of E. coli bacteria in well water (p=0.019), there was a correlation between the walls of the well and the presence of E. coli bacteria in well water (p 0.026), there is a relationship between the well lip dig and the presence of E. coli bacteria in dug well water (p=0.011), and there was a correlation between the floor of the well and the presence of E. coli bacteria in well water (p=0.030).The community is expected to reduce the level of pollution risk by monitoring and improving the non suitable construction  of wells so that the well condition remain safe and can meet the requirements. Thus there is no bacterial contamination in well water. Keywords: Well, Escherichia coli, Risk of Pollution